Revisiting nutrient management for Citrus production: to what extent does molybdenum affect nitrogen assimilation of trees? - Hippler, Franz W.R.; Boaretto, Rodrigo Marcelli; Dovis, Veronica L.; Gomes, Graziela O.F.; Quaggio, Jose A.; Quinones, Ana; Mattos Jr., Dirceu (2018)
Increasing the nitrogen (N) use efficiency of fruit trees to enhance fruit yield and decrease N rate and fertilization losses in the field is intensively discussed. Noteworthy, molybdenum (Mo) demand is likely to increase in high yielding citrus orchards. However, supply of this micronutrient through fertilization practices is not well-known. Thus, two experiments were carried out under greenhouse conditions to evaluate the nitrate reductase (NRase) activity and the Mo mobility in sweet orange plants (1-yr-old) after foliar application of Mo. For both experiments, the plants were supplied with two N levels via fertigation over 7-mo (totaling 2.8 and 17.5 g of N per plant), with Mo treatments applied in the final month. The first experiment consisted of leaf sprays to the whole plant canopy at 0 (control), 0.12, 0.60 and 1.20 g L-1 Mo. In the second experiment, the 0.60 g L-1 Mo spray was limited to one side of the canopy. The Mo supply enhanced the NRase activity either in leaves or roots and increased the nitrate uptake by roots. Consequently, the N content in the roots, twigs and leaves of plants increased. When the Mo was sprayed on one side of the canopy, the nutrient was translocated (30 - 40% from the absorbed) from the leaves to the roots, but at a lower percentage in plants grown with the highest N supply. Although the Mo concentration did not increase in leaves that did not directly receive the micronutrient spray, the NRase increased in both parts of the canopy, as well as in the roots, enhancing the N content in Citrus.